2022
DOI: 10.1080/07853890.2022.2027007
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pandemic mental and physical health as predictors of COVID-19 vaccine hesitancy: evidence from a UK-wide cohort study

Abstract: Background Although several predictors of COVID-19 vaccine hesitancy have been identified, the role of physical health and, particularly, mental health, is poorly understood. Methods We used individual-level data from a pandemic-focused investigation (COVID Survey), a prospective cohort study nested within the UK Understanding Society (Main Survey) project. In the week immediately following the announcement of successful testing of the first efficacious inoculation (Oxf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 46 publications
5
17
1
Order By: Relevance
“…[ 10 , 49 ]). Additionally, in line with [ 50 ], who found that people with a physical health condition before the pandemic were more likely to take up the offer of vaccination, we also highlighted that areas more aware of the health risk due to COVID-19 are characterised by higher uptake. We also show that areas around the largest cities are more likely to be hesitant to the vaccination, in line with [ 51 ], a cross-sectional spatial modelling study in the UK conducted prior to the mass vaccination campaign, which revealed that London, Greater Manchester and Liverpool regions and minority ethnic groups were more resistant towards a new vaccine.…”
Section: Discussionsupporting
confidence: 87%
“…[ 10 , 49 ]). Additionally, in line with [ 50 ], who found that people with a physical health condition before the pandemic were more likely to take up the offer of vaccination, we also highlighted that areas more aware of the health risk due to COVID-19 are characterised by higher uptake. We also show that areas around the largest cities are more likely to be hesitant to the vaccination, in line with [ 51 ], a cross-sectional spatial modelling study in the UK conducted prior to the mass vaccination campaign, which revealed that London, Greater Manchester and Liverpool regions and minority ethnic groups were more resistant towards a new vaccine.…”
Section: Discussionsupporting
confidence: 87%
“… 40 Chinese people have a strong sense of responsibility toward their families, and they probably hold the view that being vaccinated is an action they can do to protect their families. Moreover, emerging studies yielded mixed results on the effects of mental health on vaccine hesitancy 15 , 16 , 27 , 41 , 42 although no significant association was found between current mental health status (depression, anxiety, and insomnia) and vaccine hesitancy in this study.…”
Section: Discussioncontrasting
confidence: 74%
“…The vaccine hesitancy reported here might be attributed to lack of awareness related to cognitive impairment, lack of motivation and low levels of activity. In a minority of patients, paranoia might be a factor [ 26 , 27 ]. The lower vaccination rate for COVID-19 in individuals with a history of hospitalization for a psychiatric disorder is consistent with the literature regarding other preventive vaccines.…”
Section: Discussionmentioning
confidence: 99%